Dynamics of hydrogen liner formation in the inverse Z-pinch configuration at the MIG generator. First results on the study of the pd reaction; Proceedings of the 15th International Conference on High-Power Particle Beams, Saint-Petersburg, july 18-23, 2004 - Bystritsky V. M.; Bysritskii Vit. M.; Dudkin G. N. Gennadiy Nikolaevich; Gerasimov V. V.; Krylov A. R.; Mesyats G. A. Gennady Andreyevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Parzhitsky S. S.; Pen'kov F. M.; Ratakhin N. A.; Stolupin V. A.; et al. (2005, 2005)
В фонде НТБ ТПУ отсутствует